2008
DOI: 10.7182/prtr.18.1.d4r0564645ut6074
|View full text |Cite
|
Sign up to set email alerts
|

Optimal transplant education for recipients to increase pursuit of living donation

Abstract: Recipients spent 10 median hours learning about transplant, primarily by speaking to medical staff (2-3 hours) and reading transplant brochures (0-1 hour). Twelve percent had not received any education before coming to the transplant center. At least 75% wanted education discussing the evaluation, surgery, and medical tests required of recipients and donors, as well as common transplant-related fears. Recipients who received living donor transplants were more interested in information about donors' evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 33 publications
1
31
0
3
Order By: Relevance
“…Comprehensive education would address both the benefits and risks of deceased and living donor transplantation compared with each other, dialysis, and no treatment (15). Furthermore, quantitative and qualitative work with potential and past kidney recipients about their needs for education (16,17) recommended that educational material should address the following: (1) practical issues around the evaluation process and surgery for both recipients and donors; (2) common concerns about LDKT, including those about harm and inconvenience to donors; and (3) ways donors may benefit from LDKT. From a provider's perspective, dialysis nephrologists have indicated the importance of spending adequate time with each patient (.20 minutes) to review benefits, risks, practical issues, and concerns and to answer questions (18).…”
Section: Need For Improved Ldkt Education Outside Of Transplant Centersmentioning
confidence: 99%
“…Comprehensive education would address both the benefits and risks of deceased and living donor transplantation compared with each other, dialysis, and no treatment (15). Furthermore, quantitative and qualitative work with potential and past kidney recipients about their needs for education (16,17) recommended that educational material should address the following: (1) practical issues around the evaluation process and surgery for both recipients and donors; (2) common concerns about LDKT, including those about harm and inconvenience to donors; and (3) ways donors may benefit from LDKT. From a provider's perspective, dialysis nephrologists have indicated the importance of spending adequate time with each patient (.20 minutes) to review benefits, risks, practical issues, and concerns and to answer questions (18).…”
Section: Need For Improved Ldkt Education Outside Of Transplant Centersmentioning
confidence: 99%
“…Patients pursuing LDKT want detailed information about the evaluation, surgery, and medical tests required for recipients and donors 47. Several transplant centers have increased LDKT rates by offering formal family education programs and targeting African-Americans 48.…”
Section: Interventions Addressing Barriers To Ldktmentioning
confidence: 99%
“…4 Lung transplant or bust: patients' recommendations for ideal lung transplant education Formative studies, most commonly with kidney patients, have been undertaken to learn about the specific educational needs of patients. 5,6 For example, researchers have identified that ideal kidney transplant education should address: recipients' transplantation fears, 7 patients' quality of life and psychosocial needs, 5 and patients' readiness to accept their illness. 8 Less is known about the educational preferences of patients with end-stage lung disease.…”
mentioning
confidence: 99%